Improvement and tolerance mechanisms of Priestia megaterium to salt ions - Wang, Chunlong; Chu, Shaohua; Zhang, Dan; Zhou, Pei; You, Yimin (Frontiers in Microbiology, 2025)
IntroductionSalinity is a major abiotic stress threatening global agriculture. While some microorganisms are known to ameliorate soil salinity and promote plant growth, the underlying mechanisms, particularly for Priestia megaterium (formerly Bacillus megaterium), remain less explored.MethodsHere, we investigated the efficacy and mechanism of P. megaterium NCT-2 in improving secondary saline soil by elemental analysis, 15N tracing, gene knockout and transcriptomics.ResultsOur results demonstrated that the NCT-2 agent significantly reduced the content of key salt ions, notably NO₃−, Cl−, and Na+ in soil. Through a combination of biochemical assays, isotope tracing, and gene knockout techniques, we identified that the aerobic assimilation pathway is the primary route for nitrate metabolism in NCT-2, with the nasC and nasD genes being crucial for this process. Furthermore, transcriptomic analysis under salt stress revealed that NCT-2 employs a multi-faceted tolerance strategy, which includes enhancing sporulation, activating antioxidant defenses (e.g., CAT, SOD), assembling flagella, and forming vesicles. Concurrently, the strain upregulates central carbon metabolism (TCA cycle, glycolysis) and amino acid synthesis to fuel these adaptive responses.DiscussionThis study provides a comprehensive theoretical foundation for using P. megaterium NCT-2 in environmental remediation and identifies key genetic targets for enhancing microbial salt tolerance.